Lesões oculares observadas pela oftalmoscopia binocular indireta em gerbilos (Meriones unguiculatus) infectados com Toxocara canis - Zanandrea, Ledilma Inês Duarte Colodetti (2006)
Introduction: There are few experimental studies on ocular toxocariasis and it was recently revealed that gerbils infected with T. canis show frequent and early ocular lesions. Objectives: To follow the evolution of ocular lesions in gerbils using binocular indirect ophthalmoscopy (BIO) after oral inoculation with T. canis for 38 days. Methods: After oral inoculation of 100 embryonated eggs of T. canis, thirty six gerbils (Meriones unguiculatus) were observed with BIO in the 3rd ,10th ,17th ,24th ,31th and 38th days. Eight animals were inoculated and sacrificed after two weeks for histopathological investigation, along the ones observed after 38 days. Results: Spontaneous lesions like white spots and peripherical atrophic holes, asteroid hyalosis, coloboma and diffuse retinal pigment epithelial atrophy were noticed before the inoculation. After the inoculation the most frequent lesions were: retinal (focal and either superficial or with white centers), choroidal and vitreous hemorrhages, seen after the third day, but showing signs of receding after the 17th day. Exsudative lesions and vasculitis appeared later. DUSN and severe vitreous opacity with exsudative retinal detachment were seen once. Posterior pole and peripherical granulomas were not observed. Focal retinal pigment epithelial changes were frequent. Migrating larvae observations were rare, but its traces were more frequent. The histopathological investigation supported the BIO observations and revealed focal episcleritis, iridociclitis and dacrioadenitis, with neutrophilic and eosinophilic exsudates. Eosinophilic granuloma in the adipose tissue outside the ocular globe was also reported. Conclusion: The results show the gerbil model for ocular toxocariasis after oral inoculation with T. canis, although not showing the typical lesions of human toxocariasis, specially the pseudotumorals seen as posterior pole or peripherical granulomas, can be very useful for experimental investigations of ocular toxocariasis, due to its frequency and early lesions.